Uncovering the Advantages of Foam Dressings with Active Ingredients - Chrysostomou, Daniela; Papanikolaou, Georgios E; Boshoff, Lorraine; Mbele, Thandazi; Pokorná, Andrea; Holubová, Adéla; Wagener, Frank A D T G; Cremers, Niels A J (Pharmaceuticals (Basel, Switzerland), 2025)
Background/Objectives: Foam dressings are designed for their ability to manage exudate and are selected to optimize wound repair. Various foam dressings are available, ranging from basic polyurethane to more sophisticated options, incorporating active components to combat infections or foster healing. This study investigates the requirements for the most suitable foam dressing through a combination of field research, laboratory testing, and clinical evaluation. Methods: We tested 17 foam dressings commonly used by wound care professionals while attending an international conference. An effective foam dressing should absorb wound fluid for several days, as wound care professionals value absorption and retention capacity, often favoring less frequent changing dressings, preferably twice a week or even weekly. Results: The foam dressings tested can absorb the expected amount of exudate typically produced by different wound types. There is some variability in retention capacity and product prices, resulting in differences in cost-effectiveness among products. In addition, some dressings are enriched with active ingredients that can accelerate healing through their antimicrobial and anti-inflammatory properties, such as foam dressings infused with silver or honey. A honey-based foam dressing was evaluated in a clinical survey involving eight wound care specialists, and four clinical cases with varying wound pathologies were discussed in more detail to highlight its key properties. Conclusions: Ideally, a foam dressing should have adequate absorption and retention capacities, effectively resolve and prevent infections, protect against external trauma, ensure optimal patient comfort without damaging newly formed granulation tissue, accelerate wound healing processes, and reduce wound care time (e.g., remaining in place for 7 days). Together, these factors make honey- or silver-loaded foam dressings more cost-effective than plain dressings due to their antimicrobial activities and ability to nourish tissues.
Keywords: honey; wound healing; cost–benefit analysis; silver; exudates; active dressings; polyurethanes; bandages; foam dressings; wounds